Empirical model of TEC response to geomagnetic and solar forcing over Balkan Peninsula. (January 2018) - Mukhtarov, P.; Andonov, B.; Pancheva, D.
Abstract: An empirical total electron content (TEC) model response to external forcing over Balkan Peninsula (35°N-50°N; 15°E-30°E) is built by using the Center for Orbit Determination of Europe (CODE) TEC data for full 17 years, January 1999 - December 2015. The external forcing includes geomagnetic activity described by the K p -index and solar activity described by the solar radio flux F10.7. The model describes the most probable spatial distribution and temporal variability of the externally forced TEC anomalies assuming that they depend mainly on latitude, K p -index, F10.7 and LT. The anomalies are expressed by the relative deviation of the TEC from its 15-day mean, rTEC, as the mean value is calculated from the 15 preceding days. The approach for building this regional model is similar to that of the global TEC model reported by Mukhtarov et al. (2013a) however it includes two important improvements related to short-term variability of the solar activity and amended geomagnetic forcing by using a "modified" Kp index. The quality assessment of the new constructing model procedure in terms of modeling error calculated for the period of 1999–2015 indicates significant improvement in accordance with the global TEC model (Mukhtarov et al., 2013a). The short-term prediction capabilities of the model based on the error calculations for 2016 are improved as well. In order to demonstrate how the model is able to reproduce the rTEC response to external forcing three geomagnetic storms, accompanied also with short-term solar activity variations, which occur at different seasons and solar activity conditions are presented. Highlights: Empirical model of TEC response to external forcing over Balkan Peninsula is constructed. External forcing includes geomagnetic activity and short-term variability of the solar radiation. Quality assessment of the constructing model procedure and the model short-term prediction ability has been evaluated.